Implementación de seguridades mediante criptografía para servidores basados en software libre, para el laboratorio de redes de la carrera de ingeniería en informática y sistemas computacionales, durante el período 2013 - Anchatipán Navas, Danilo Fernando (2015)
This research was based in the implementation of security trough cryptography to mail, based on free software for the network laboratory of career Engineering in Computing and Computational Systems of the Technical University of Cotopaxi, It was considered the insecurity that exist to the send and receive clear emails, resolving this problem whit secure email application onto a Linux platform. The research was developed, in base to information collected from books published, for computer security experts; the survey, was used survey as a technique to get the actual requirements over dwellers that use the cryptography by emails. In addition to the application, was used diverse technologies free software, as the email client Thunderbird, enigmail to encrypt and decrypt messages, operating system Centos and user accounts of several providers email. Whit this implementation was got assure the confidentiality, integrity and availability messages.